Examining the ICT access effect on socioeconomic development: the moderating role of ICT use and skills. Issue 1 (2nd January 2017) - Alderete, María Verónica
ABSTRACT: This paper examines the role that Information and Communication Technologies (ICT) play in the socioeconomic development of countries. The proposed model analyzes the relationship between ICT access (available ICT infrastructure and individual's access to ICT), ICT use (ICT intensity and usage, and ICT skills), and socioeconomic development. The methodology employed consists of a Structural Equation Model (SEM). To achieve this goal, country-level data across 163 countries for the year 2013 is used from developing to developed countries. Results obtained indicate the moderating role of ICT use and skills in the relationship between ICT access and the socioeconomic development. The ICT usage and ICT skills enhance the effect of ICT access on the socioeconomic development. The model is robust with respect to the development level.